Molecular docking and molecular dynamics simulation of glycyrrhizic acid in multitarget agents as potential inhibitors of respiratory influenza viruses - Aarati Ramesh Supekar, Santosh Bhujbal, Rashmi Yadav (Journal of Applied Pharmaceutical Science, 2025)
Glycyrrhizic acid (GA), a key component of licorice root, has demonstrated various antiviral properties, including potential efficacy against influenza viruses. Using molecular docking, this study aims to elucidate GA’s binding affinity and stability with multiple target proteins associated with respiratory influenza viruses. Utilizing state-of-the-art computational techniques, we investigated the interactions between GA and key viral protein targets, including the ATP-bound state of BiP (5E84), main protease (Mpro) (6LU7), spike receptor binding domain (6LZG), RNA-dependent RNA polymerase (6M71), spike glycoprotein (6VSB), NSP15 endonuclease (6VWW), Nsp9 RNA-binding protein (6W4B), papain-like protease (6W9C), and neurominadase from H1N1 (5NZ4) implicated in respiratory influenza infection. Our findings clarify GA’s binding modes within the active sites of these targets, shedding light on its inhibitory potential against viral replication. We study the stability and dynamics of the GA-protein complexes using detailed molecular dynamics simulations. This helps us understand how their antiviral activity works. These computational insights provide valuable guidance for the rational design of GA-based therapeutics, as well as promising avenues for further experimental validation and drug development efforts.
Keywords: Glycyrrhizic acid, multitarget agents, respiratory influenza viruses, antiviral activity, computational modelling, molecular docking, and molecular dynamics simulation